2023
DOI: 10.3390/biology12040546
|View full text |Cite
|
Sign up to set email alerts
|

Date Palm Waste Compost Application Increases Soil Microbial Community Diversity in a Cropping Barley (Hordeum vulgare L.) Field

Abstract: Application of date palm waste compost is quite beneficial in improving soil properties and crop growth. However, the effect of its application on soil microbial communities is less understood. High-throughput sequencing and quantitative real-time PCR (qPCR) were used to evaluate the effect of compost application on the soil microbial composition in a barley field during the tillering, booting and ripening stages. The results showed that compost treatment had the highest bacterial and fungal abundance, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…However, elongation at break decreased with most increased fiber content levels. This balance between tensile strength and morphology, underlined by the SEM findings, emphasizes the critical importance of precise fiber treatments [121,122] and loading levels in developing sustainable bioplastics. Another study developed natural fiber-reinforced polymer matrix composites using two different sizes of EFB fibers (605 μm and 633 μm) and acrylic thermoplastic resin.…”
Section: Product Diversification and Value-addition From Palm Oil By-...mentioning
confidence: 82%
See 1 more Smart Citation
“…However, elongation at break decreased with most increased fiber content levels. This balance between tensile strength and morphology, underlined by the SEM findings, emphasizes the critical importance of precise fiber treatments [121,122] and loading levels in developing sustainable bioplastics. Another study developed natural fiber-reinforced polymer matrix composites using two different sizes of EFB fibers (605 μm and 633 μm) and acrylic thermoplastic resin.…”
Section: Product Diversification and Value-addition From Palm Oil By-...mentioning
confidence: 82%
“…Furthermore, EFB fibers are composted into nutrient-rich fertilizers, enhancing sustainable agriculture practices [121,122], and used in the production of green materials and biomaterials [123,124]. The morphology of palm oil flower and fruit fibers was studied using scanning electron microscopy, revealing distinct characteristics (Figure 4(a)-(d)).…”
Section: Product Diversification and Value-addition From Palm Oil By-...mentioning
confidence: 99%
“…In terms of the microbiological context, the tested sandy soil exhibited a higher organic carbon content, and all treatments (chicken manure compost and composted date palm tree wastes) showed an increase in the number of microorganisms compared to the control [132]. Ghouili et al (2023) [295] demonstrated that the application of date palm waste compost significantly improved soil microbial diversity and richness during the tillering, booting, and maturing stages of barley growth. In particular, palm compost fertilization significantly raised the fungal richness and diversity indices relative to the control, while the bacterial richness and diversity indices decreased significantly.…”
Section: Effects Of Compost Application On Soil Propertiesmentioning
confidence: 99%